Displacement in the image of war In the poetry of Qais bin Al-Khatim (Journal of the College of Basic Education, 2022)
This research studies an artistic feature that was dyed with the poetry of Qais bin Al-Khatim, one of the prominent poets of the pre-Islamic era, who recorded in his divan good eloquence and linguistic structures of great quality and rhetorical expression. The Holy Qur’an was revealed to them in their own language.